2003
DOI: 10.1097/01.hjr.0000070200.72977.c6
|View full text |Cite
|
Sign up to set email alerts
|

Hair Loss, Insulin Resistance, and Heredity in Middle-aged Women. a Population-based Study

Abstract: According to the results of this study, female AGA (grade II or III on Ludwig's scale) was quite common among Finnish women aged 63 years. Our results support the hypothesis that women with some markers of insulin resistance have significantly increased risk for female AGA. Paternal history of alopecia seemed to be more common in female AGA compared to women with normal or minimal loss of hair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
76
3
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 20 publications
5
76
3
3
Order By: Relevance
“…The Finnish study reported the same region with the previous study the prevalence rates of impaired glucose regulation and insulin resistance were found to be significantly higher among the women with hair loss compared to women with normal hair [10]. However, on contrary these studies in case controlled study from Egypt no association was observed between AGA and insulin resistance in young aged group including both gender [11].…”
supporting
confidence: 53%
“…The Finnish study reported the same region with the previous study the prevalence rates of impaired glucose regulation and insulin resistance were found to be significantly higher among the women with hair loss compared to women with normal hair [10]. However, on contrary these studies in case controlled study from Egypt no association was observed between AGA and insulin resistance in young aged group including both gender [11].…”
supporting
confidence: 53%
“…Therefore, it was difficult to compare their results with those of other studies. Matilainen et al 6 found that the prevalence of current smoking among women with extensive hair loss (Ludwig grades ՆL-II to L-III) did not differ from those with normal or minimal hair loss (P=.92). However, the main objective of the study was not tailored to smoking history, and no definition of smoking was addressed.…”
Section: Commentmentioning
confidence: 96%
“…6,7 Severi et al 7 reported a lower risk of AGA among current smokers (OR, 0.86; 95% CI, 0.54-1.38) and exsmokers (OR, 0.91; 95% CI, 0.65-1.29), although the results were not statistically significant. Nevertheless, details of smoking history were lacking, and the age at onset of AGA was unknown.…”
Section: Commentmentioning
confidence: 98%
See 1 more Smart Citation
“…tarafından 63 yaşındaki 324 kadın ile yapılan toplum tabanlı KOHORT bir çalışmada incelenmiştir. Çalışmada Ludwig 2 ve 3 düzeyinde AGA tespit edilen 97 kadında, bel, boyun çevresi ölçümleri, abdominal obezite, açlık insülin düzeyi ya da üriner albumin/kreatinin oranı gibi insülin direnci ile ilişkili parametreler, minimal dökülmesi olan (Ludwig 1) veya saç dökülmesi olmayan 221 kadına oranla daha yüksek bulunmuştur 17 . Daha sonra Hirsso ve ark.…”
Section: Discussionunclassified